The incidence and outcome of respiratory distress syndrome in preterm babies in relation to administration of antenatal corticosteroids - Abdul Jaleel, Shermin Nasreen; Sarojum, Bindu; Sasidharan, Bindusha; Krishnan, Priya Gopala (Indian Journal of Child Health, 2018)
Background: Premature infants have a higher incidence of respiratory distress syndrome (RDS), which is one of the main causes of early neonatal mortality. Objectives: The objective is to study the incidence and outcome of RDS in preterm babies <34 weeks of gestation born to mothers who had received antenatal corticosteroids (ACS). Methodology: A prospective observational study was conducted among preterm babies from January 2015 to December 2015 in a tertiary care hospital of South India. Details of the mothers with a period of gestation 34 weeks or less who had received ACS were recorded. Results: The study population included 749 preterm babies (<34 weeks) delivered in our hospital. Among them, 698 (93.2%) mothers received two doses of ACS and 51 (6.8%) received only a single dose of ACS. Neonates whose mothers received two doses of ACS had a significantly lower incidence of RDS (27.6% vs. 100%, p<0.001), lower rate of mechanical ventilation (45% vs. 72.5%, p<0.001), and higher survival rate (87% vs. 68.6%, p=0.001) than neonates whose mothers received a single dose of ACS. The occurrence of RDS is highest in 26